Demarcation energy properties of regenerated fiber Bragg grating sensors in few-mode fibers - Nazal, Nurul Asha Mohd; Lai, Man Hong; Lim, Kok Sing; Gunawardena, Dinusha Serandi; Chong, Wu Yi; Yang, Hang Zhou; Ahmad, Harith (International Society for Optical Engineering, 2018)
In this work, thermal regeneration of fiber Bragg gratings inscribed in single-mode fibers, two-mode step index fibers and four-mode step index fibers is performed, where the single-mode fibers are used as the reference in the analysis. Specifically, we investigate the behavior of the thermal decay, recovery and eventually the permanent erasure of the gratings in the temperature range from 25 to 1300°C. In the domain of demarcation energy, the thermal responses of the gratings can be normalized and they share similar characteristic curves despite the different temperature ramping rates used in the annealing treatment. It is found that the demarcation energy at the regeneration point and the attempt-to-escape frequency for each grating can be associated with the confinement factors of the fibers. The finding in this work has provided a new insight in the manufacture of regenerated fiber Bragg grating sensors by using few-mode fibers for multiparameter sensing in high temperature environments.